Comparison of Early Outcomes with Three Approaches for Combined Coronary Revascularization and Carotid Endarterectomy - Dönmez,Arzu Antal (2016)
Abstract Objective: This study aims to compare three different surgical approaches for combined coronary and carotid artery stenosis as a single stage procedure and to assess effect of operative strategy on mortality and neurological complications. Methods: This retrospective study involves 136 patients who had synchronous coronary artery revascularization and carotid endarterectomy in our institution, between January 2002 and December 2012. Patients were divided into 3 groups according to the surgical technique used. Group I included 70 patients who had carotid endarterectomy, followed by coronary revascularization with on-pump technique, group II included 29 patients who had carotid endarterectomy, followed by coronary revascularization with off-pump technique, group III included 37 patients who had coronary revascularization with on-pump technique followed by carotid endarterectomy under aortic cross-clamp and systemic hypothermia (22-27ºC). Postoperative outcomes were evaluated. Results: Overall early mortality and stroke rate was 5.1% for both. There were 3 (4.3%) deaths in group I, 2 (6.9%) deaths in group II and 2 (5.4%) deaths in group III. Stroke was observed in 5 (7.1%) patients in group I and 2 (6.9%) in group II. Stroke was not observed in group III. No statistically significant difference was observed for mortality and stroke rates among the groups. Conclusion: We identified no significant difference in mortality or neurologic complications among three approaches for synchronous surgery for coronary and carotid disease. Therefore it is impossible to conclude that a single principle might be adapted into standard practice. Patient specific risk factors and clinical conditions might be important in determining the surgical tecnnique.